Corticosteroids for dengue - why don't they work? - Thi Hanh Tien Nguyen; Than Ha Quyen Nguyen; Tuan Trung Vu; Jeremy Farrar; Truong Long Hoang; Thi Hoai Tam Dong; Van Ngoc Tran; Khanh Lam Phung; Marcel Wolbers; Stephen S Whitehead; Martin L Hibberd; Bridget Wills; et al. (Public Library of Science (PLoS), 2013)
Dysregulated immune responses may contribute to the clinical complications that occur in some patients with dengue.In Vietnamese pediatric dengue cases randomized to early prednisolone therapy, 81 gene-transcripts (0.2% of the 47,231 evaluated) were differentially abundant in whole-blood between high-dose (2 mg/kg) prednisolone and placebo-treated patients two days after commencing therapy. Prominent among the 81 transcripts were those associated with T and NK cell cytolytic functions. Additionally, prednisolone therapy was not associated with changes in plasma cytokine levels.The inability of prednisolone treatment to markedly attenuate the host immune response is instructive for planning future therapeutic strategies for dengue.